The Integration of Modern Technology in Railway Operations : A Case of Tanzania's Standard Gauge Railway - Vicent , Yasinta Richard (Journal of Industrial Engineering & Management Research, 2025)
This study examined the impact of modern technology integration on the operational efficiency of Tanzania’s Standard Gauge Railway (SGR). With growing demand for reliable, safe, and efficient rail services, the research evaluated how automation, safety and security systems, and digital ticketing platforms influence service quality and operational performance. Data were collected from 76 participants including engineers, operations managers, security personnel, ticketing officers, and passengers using structured questionnaires, with 68 responses analysed. A descriptive quantitative design was employed, utilizing descriptive statistics to capture perceptions of technology use and multiple linear regression to explore relationships between technology variables and operational efficiency. Results showed positive perceptions of technological advancements, highlighting improvements in scheduling accuracy, fraud reduction, and passenger management. However, regression analysis revealed that while technology variables had positive effects, none were statistically significant predictors of efficiency at the 5% level. Multicollinearity, particularly between automation and safety systems, was noted, indicating overlapping contributions. The study concludes that although technology has enhanced key SGR functions, its full potential remains untapped. Recommendations include improving system interoperability, enhancing staff training, and adopting integrated strategies for operational advancement. These findings offer valuable guidance for policymakers and railway stakeholders aiming to modernize and optimize Tanzania’s rail transport.